Opening catalytic sites in the copper-triazoles framework via defect chemistry for switching on the proton reduction - Wang, Zhao-Di; Zang, Ying; Liu, Zhi-Juan; Peng, Peng; Wang, Rui; Zang, Shuang-Quan (Applied catalysis. B, Environmental, 2021)
[Display omitted] •A defect-engineering strategy to construct the intrinsic defects in metal-organic frameworks was proposed.•The accurate chemical formulas of defective MOF were obtained by simply characterization techniques.•The intrinsic deficiency activates the inert framework to trigger their catalytic performance for outstanding H2 evolution. Defective metal-organic frameworks (MOFs) materials have ignited intensive attention in the field of photocatalytic H2 evolution. In this work, we applied a defect-engineering strategy to construct intrinsic defects in Cu-MOF, which gives birth to the excellent photocatalytic ability for proton reduction. Furthermore, the fine characterizations give the exact molecular formula of the defective Cu-MOF (copper-based metal-triazolate material, termed as MET-Cu-D). The intrinsic deficiency, ligand-vacancies of 1H-1,2,3-triazole, is generated in situ during the synthesis process, which triggers the catalytic activity of unsaturated Cu-sites for the outstanding H2 evolution performance. Photocatalysis results indicate that MET-Cu-D exhibited an excellent hydrogen evolution rate of 12.91 mmol g−1 and catalytic stability. This study provides a new train of thought for the design of defective MOFs to promote the further development of solar-hydrogen fuel.